2009
DOI: 10.1177/1091581809338077
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Calmodulin Regulate Mercury-induced Phospholipase D Activation in Vascular Endothelial Cells

Abstract: Earlier, we reported that mercury, the environmental risk factor for cardiovascular diseases, activates vascular endothelial cell (EC) phospholipase D (PLD). Here, we report the novel and significant finding that calcium and calmodulin regulated mercury-induced PLD activation in bovine pulmonary artery ECs (BPAECs). Mercury (mercury chloride, 25 microM; thimerosal, 25 microM; methylmercury, 10 microM) significantly activated PLD in BPAECs. Calcium chelating agents and calcium depletion of the medium completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Similarly, Seppänen et al (2004) found no evidence for promotion of direct lipid peroxidation by MeHg. Other in vitro studies have provided support for the hypothesis that MeHg can interfere with signal transduction and proper endothelial cell function [both in human umbilical cord endothelial cells (Hagele et al 2007; Mazerik et al 2007; Peltz et al 2009) and bovine endothelial cells (Kishimoto et al 1995; Ohno et al 1995)], which may influence atherosclerosis. However, three studies support a direct mechanism for MeHg’s role in oxidation, showing that antioxidants and compounds that remove ROS can mitigate MeHg toxicity (Gasso et al 2001; Park et al 1996; Welsh 1979).…”
Section: Workhop Findings and Near-term Recommendationsmentioning
confidence: 94%
“…Similarly, Seppänen et al (2004) found no evidence for promotion of direct lipid peroxidation by MeHg. Other in vitro studies have provided support for the hypothesis that MeHg can interfere with signal transduction and proper endothelial cell function [both in human umbilical cord endothelial cells (Hagele et al 2007; Mazerik et al 2007; Peltz et al 2009) and bovine endothelial cells (Kishimoto et al 1995; Ohno et al 1995)], which may influence atherosclerosis. However, three studies support a direct mechanism for MeHg’s role in oxidation, showing that antioxidants and compounds that remove ROS can mitigate MeHg toxicity (Gasso et al 2001; Park et al 1996; Welsh 1979).…”
Section: Workhop Findings and Near-term Recommendationsmentioning
confidence: 94%
“…In regard to general brain health, both forms of Hg (Me- and Et-Hg) have been found to cause Hg-induced vasculo-toxicity and resulting reduced blood flow in the brain [117,118,119]. Both cerebral and cerebellar decreased blood flow can result from Hg exposure.…”
Section: Research Evidencementioning
confidence: 99%
“…The amplitude and kinetics of both transient and sustained phases of hypoxia-induced pulmonary vasoconstriction are not significantly changed in isolated perfused lungs from BKα –/– mice or hemogenase-2 knock-out mice (HO-2 –/– ). These data indicate that, although BK Ca channels are regulated by HO-2-mediated redox changes, the HO-2/BK Ca complex may not serve as an oxygen sensor in acute hypoxia-induced pulmonary vasoconstriction (218, 245). …”
Section: K+ Channels and Transportersmentioning
confidence: 90%